PTU-111 Does a 2 week break from colonoscopy practice impact on performance?. (June 2019) - Siau, Keith; Disney, Ben; Cheung, Danny; Murugananthan, Aravinth; Kotecha, Deevia; Verma, Ajay; Thoufeeq, Mo; Shetty, Sharan
Abstract : Introduction: Although breaks in colonoscopy practice have been shown to adversely affect trainee performance, 1 this has not been studied in independent endoscopists. We aimed to evaluate the impact of a ≥2wk break in colonoscopy on the completion metrics of independent practitioners. Methods: We performed a retrospective analysis of electronic colonoscopy databases in six NHS Trusts within East Midlands, West Midlands and South Yorkshire. Procedures between 2016–2018 were extracted by endoscopist identifier and in time order. A break was defined as a 14d+ interval between procedures. For each break, 20 pre and 20 post break procedures were identified. Breaks were excluded if a ≥2wk interval occurred within the 20 pre-break procedures, and if any of the 20 pre-break procedures occurred within 14d of another break or overlapped with any post-break procedures. Study outcomes included: 1) the Performance Indicator of Colonic Intubation (PICI), 2 a composite endpoint integrating completion, sedation and discomfort metrics, and 2) the unadjusted caecal intubation rate (CIR). Pairwise comparisons between pre and post break data were made for pooled data and by endoscopist using Wilcoxon signed rank tests. Results: 352 breaks undertaken by 113 endoscopists were eligible for analysis, comprising 14, 080 procedures. The median break interval was 18d (IQR 14–24). Baseline comparisons of the pre and post groups revealed no significant differences in age, gender or proportion of Bowel Cancer Screening cases. Between pre and post break periods, mean PICI fell from 82.1% to 80.0% (P<0.001) and mean CIR from 93.8% to 92.5% (P=0.003). Trends in PICI with 10-procedure moving averages relative to the break (Abstract PTU-111 figure 1) did not suggest reversion to baseline rates after 20 post-break procedures. At endoscopist-level, breaks were associated with a small but significant reductions in median PICI (86.7% to 85.0%, P<0.001) and CIR (95.0% to 92.5%, P=0.004), with 58.4% of endoscopists demonstrating a decrement in PICI. There was no significant correlation between the duration of the break and the difference in PICI (Pearson coefficient -0.014, P=0.788). Conclusions: A break in practice of ≥2wks appears to result in a small but statistically significant decrement in colonoscopy completion metrics as measured by PICI and CIR. References: Jorgensen JE. Gastrointest Endosc 2013; 78:503–9. Valori RM. Endoscopy 2018;50:40–51.